Impact of Charred Firewood on Selected Soil Properties of Regosols in Jaffna Peninsula - Shayanthan, A.; Gnanavelrajah, N. (Jaffna Science Association, 2012)
Charred Firewood (CF) could be used to enhance agricultural productivity by improving soil quality. A laboratory incubation study was conducted for 12 weeks to find out the effect of application of CF alone and in combination with inorganic fertilizers on selected properties of Regosols of Jaffna peninsula. Treatments were T0 (control), T1 (CF), T2 (NPK fertilizer), and T3 (½ CF + ½ NPK fertilizer). Complete randomized design was used with three replicates. Results of incubation experiment with different treatments indicated that pH of soil significantly increased in T1 (CF) and decreased in T2 (NPK fertilizer). Available N was significantly higher in T3 (½ CF + ½ NPK fertilizer) and T2 (NPK fertilizers) compared T1 and T0. Available P was significantly increased in T2 (NPK fertilizer) followed by T1 (CF) and T3 (½ CF + ½ NPK fertilizer) compared T0. Available K was significantly increased in T1 (CF), T3 (½ CF + ½ NPK fertilizer) and T2 (NPK fertilizer) compared to control. EC was significantly increased in NPK fertilizer followed by T3 (½ CF + ½ NPK fertilizer) and T1 (CF) compared to control. Cation exchange capacity, water holding capacity and microbial biomass carbon were significantly increased with T1 (CF) compared to other treatments. Results therefore indicate that CF has alone has a negative effect on soil pH during initial statge. CF has potential to enhance the soil fertility parameters such as nutrient availability, water holding capacity, cation exchange capacity and microbial biomass in Regosols of Jaffna Peninsula.
Keywords: Regosols; CF; Soil nutrients; Soil properties